Pendidikan Khusus Profesi Advokat Dewan Pimpinan Nasional Persatuan Advokat Indonesia Dan Profesi Advokat Berdasarkan Pasal 3 Ayat (1) Huruf F Undang - Undang Republik Indonesia Nomor 18 Tahun 2003 Tentang Advokat - Tedy Subrata (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Special Education for the Advocate Profession (PKPA) is a mandate from Law of the Republic of Indonesia Number 18 of 2003 concerning Advocates. Special Education for the Advocate Profession is a form of education that must be followed by someone with a bachelor's degree with a higher legal education background. Special Education for the Advocate Profession (PKPA) has relevance to the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System (SISDIKNAS) which states that the types of education consist of general, vocational, professional, vocational, religious and special education. This Community Service activity aims to produce professional lawyers who are reliable, independent and responsible so that they are able to appear as enforcers of justice in administering justice honestly and in accordance with legal objectives, namely, legal justice, legal benefits and legal certainty for all by enforcing equality at the forefront. before the law. This activity was attended by 30 (thirty) prospective advocate participants which was held on October 14 2023 at Tangerang Raya Tiga Raksa University, Tangerang Regency. The method used by Service Learning (SL) is intended to integrate learning into the Special Education for the Advocate Profession (PKPA) or the partnership of the National Leadership Council of the Indonesian Advocates Association (DPN PERSADIN) with the Faculty of Law, University of Greater Tangerang (UNTARA). Apart from that, the Participatory Action Research (PAR) approach is oriented towards empowering participants in Special Education for the Advocate Profession (PKPA). This is due to the need and resolution of legal problems in society. Higher education officials must place society as the main actor in development and change. The result of this activity is to give birth to the profession of advocates and provide an understanding that Advocates are a profession that is noble, free, independent and responsible in upholding the law, and that the activities of this profession are guaranteed and protected by law for the sake of implementing the Rule of Law.